Czy każda zmiana barwnikowa tęczówki jest czerniakiem? Opis przypadku - Delong, Gabriela; Smoliński, Artur; Gierek-Ciaciura, Stanisława (Klinika Oczna / Acta Ophthalmologica Polonica, 2004)
In this paper authors present a history and clinical findings of 78 years old man with suspicion of iris melanoma. Malignant melanoma accounts for 70% of cell malignant tumors of the eye. The paper also contains short review of the most important clinical characteristic, diagnostic and treatment of iris melanoma.